2009
DOI: 10.1007/s00774-009-0091-5
|View full text |Cite
|
Sign up to set email alerts
|

Variation in lumbar spine bone mineral content by age and gender in apparently healthy Indians

Abstract: The aim of this study was to assess variation in bone mass from childhood through later age and to examine bone health status of Indian males and females. Lumbar spine (LS) bone mineral content (BMC) was measured by dual energy X-ray absorptiometry of lumbar vertebrae (L1-L4) in 683 males and 858 females (5-70 years) from Pune, India and apparent bone mineral density (BMAD) was calculated. A cubic regression model was fitted to describe the change in bone mineral content (BMC) with age in males and females sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Moreover, unwholesome food habits in adolescents like consumption of fried foods and bakery items, contribute to low calcium intakes in this age group (Chakravarty and Sinha 2002;Bhatia 2008;Tupe and Chiplonkar 2010). Furthermore, considering the low bone mass attained by Asians during childhood (Kadam et al 2009;Ranathunga et al 2009), adequate calcium intake with high bioavailability is necessary.…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, unwholesome food habits in adolescents like consumption of fried foods and bakery items, contribute to low calcium intakes in this age group (Chakravarty and Sinha 2002;Bhatia 2008;Tupe and Chiplonkar 2010). Furthermore, considering the low bone mass attained by Asians during childhood (Kadam et al 2009;Ranathunga et al 2009), adequate calcium intake with high bioavailability is necessary.…”
Section: Introductionmentioning
confidence: 95%
“…In India, the female-to-male hip fracture ratio is nearly one to one [4], whereas a ratio of 2.3 is observed worldwide [5]. Studies have shown that 24.3% of healthy Indian men have low BMD [6], and Indians have a lower bone mass at a younger age [6].…”
Section: Introductionmentioning
confidence: 96%
“…reported low vitamin D status in this population [18]. There is evidence of South Asian women having compromised bone health, possibly due to poor vitamin D status [19][20][21].…”
Section: Introductionmentioning
confidence: 97%